Prototype Sistem Penyiram Sayuran Bayam Otomatis Berbasis Microcontroller Atmega328p - Jajang Nurjaman (Jurnal Bangkit Indonesia, 2019)
The development and progress of technology today is very rapid, with the progress in the field of science and technology, producing new innovations. Even in the automotive industry, and the food industry, many use the help of automated robots. Especially in the field of agriculture the use of automatic technology is very necessary because in terms of difficulties in working on land and plant care. Watering is the main thing in managing vegetables. Often watering vegetables takes a long time, and requires control in the water pump so that when the water in the container is no longer available, there is a jim at the water pump. Prototype design of ATMEGA328P Microcontroller Automatic Spinach Watering System, which aims to assist farmers in watering spinach vegetables. Because this tool can monitor watering automatically. by using a Soil Moisture Hygrometer that will detect the level of moisture in the soil, so that watering will be stopped automatically when the water content in the soil is wet.